Hudson Taylor and the China Inland Mission the growth of a work of God - Taylor, Howard; China Inland Mission; Taylor, Mary Geraldine, 1862-1949 (London, UK China Inland Mission, 1918)
Includes bibliographical references and index.
Copy 1 donated by Mr A. Meers, student 1964-65. Copy 2 donated by John Dickson, Dec. 2002.
Keywords: Missions -- biography; China -- missions